Postsecondary education gender disparities among Inuit in Alaska: A symptom of male malaise? - Kleinfeld, Judith; Andrews, Justin (Études/Inuit/Studies, 2006)
AbstractFar more Inuit women in Alaska are pursuing postsecondary education compared to Inuit men. Among Inupiat in Alaska, only 28% of students pursuing baccalaureate degrees at the University of Alaska are male, and the proportion of males receiving baccalaureate degrees declined from 2000 to 2003. Among Yupiit, 30% of students pursuing baccalaureate degrees are male. Similar gender disparities occur in programs for high school students designed to prepare academically able Indigenous students for college. This phenomenon can be interpreted either as a sign of “male malaise,” of disengagement from education and the wage employment for which education is a preparation, or as a functional adaptation to a mixed wage and subsistence way of life where education and particularly higher education is less important to Inuit males than females. To examine support for the explanation of “male malaise,” we compare two Inuit regions of Alaska, the Inupiaq region of Northwest Alaska, where the regional Native corporation has emphasized providing employment within the region through the Red Dog Mine, and the Yup’ik region of southwestern Alaska, which has low numbers of jobs, particularly outside the regional hub of Bethel. In Northwest Alaska, 49% of young Inuit men, ages 22 to 29, described themselves in the 2000 census as either “unemployed” or “out of the labor force.” In Southwest Alaska, 48% of young Inuit men said the same thing. These patterns support the explanation of “male malaise.” However, community studies, which allow fine-grained, household analyses of male and female participation in the wage and subsistence economies are needed to distinguish between these two explanations or suggest other interpretations.